PERANAN KARANG TARUNA DALAM MENGEMBANGKAN SIKAP MENTAL GENERASI MUDA : Studi Kasus di Karang Taruna Bhina Jaya Bhakti Desa Jayagiri Kecamatan Lembang - Admadi, Surya (2015)
The major of human resources and the nation's fundamental capital all at once within against global challenges is young generations. The young generations, all of them, they will continue an estaffete cane of state development later. The kind of development aspect such as economic aspect, government aspect, cultural aspect or aspect of nation's character. Development of young generations within cultivate or develop their mental attitude is one of a lot efforts that could to do for increasing self-quality of young generations, thus it can make responsibility about their due and duties, and then young generations being active along their nation's life. This research based on four questions formula, consist of (1) Action plan of KarangTarunaBhina Jaya Bhakti Youth Group; (2) The methods which used by KarangTarunaBhina Jaya Bhakti Youth Group in order to develop mental attitude of young generations; (3) The obstacles which deal by KarangTarunaBhina Jaya Bhakti Youth Group in order to develop mental attitude of young generations; (4) The efforts which deal by KarangTarunaBhina Jaya Bhakti Youth Group in order to develop mental attitude of young generations. This reserach use qualitative approach with case study method. The data coming by interview, observation, and study documentation. There are results of the research: (1) Action plan of KarangTarunaBhina Jaya Bhakti Youth Group divided into three categories, that is yearly program, monthly program, and weekly program. Those program have variety event, such as training, work visiting between young group's unit, charity, and economic creative event; (2) The methods that used by KarangTarunaBhina Jaya Bhakti Youth Group such as personal approach, outbond program, and then try to always making pleasure surroundings organization; (3) The obstacle, that is internal factors and external factors. About the internal factor, included a bustle of the members, and external factor included fund restrictiveness and facility, after that the obstacle is uninterested from society to karangtaruna young groups, especially about the action plan; (4) the effort which deal byKarangTarunaBhina Jaya Bhakti Youth Group in order to develop mental attitude of young generations through by job visiting to the members for give motivation and encouragement, especially to all of non active members.